2014
DOI: 10.1177/0363546514559912
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Meniscal and Articular Cartilage Injuries in Children and Adolescents With Timing of Anterior Cruciate Ligament Reconstruction

Abstract: Delayed ACL reconstruction increased the risks of secondary meniscal and chondral injuries in this population of pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
246
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(259 citation statements)
references
References 26 publications
6
246
2
5
Order By: Relevance
“…Principle # 1: Delaying surgery until skeletal maturity is often an ineffective strategy Numerous reports [2][3][4][5][6] have outlined the potential for further injury to the knee by delaying surgery after ACL injury in the skeletally immature patient. Although growth arrest is a concern and more problematic in the youngest patients, the long-term consequences of irreparable meniscus or cartilage damage due to an unstable knee are equally concerning.…”
Section: Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Principle # 1: Delaying surgery until skeletal maturity is often an ineffective strategy Numerous reports [2][3][4][5][6] have outlined the potential for further injury to the knee by delaying surgery after ACL injury in the skeletally immature patient. Although growth arrest is a concern and more problematic in the youngest patients, the long-term consequences of irreparable meniscus or cartilage damage due to an unstable knee are equally concerning.…”
Section: Principlesmentioning
confidence: 99%
“…Similarly, Anderson et al [6] reviewed patients younger than 17 years (median age 14) who underwent ACLR and found that patients that waited for surgery in the subacute (6-12 weeks) and chronic (>3 months) groups had a 1.45 and 2.82 times, respectively, higher odds of lateral meniscal tear severity according to the International Society of Arthroscopy and Knee Surgery and Orthopaedic Sport Medicine (ISAKOS) meniscal classification system. The adjusted odds ratio for increased severity of medial meniscal tears included time to surgery >3 months, and the risk factor for a chondral injury and for an increased grade of chondral injury also included increased time to surgery >3 months.…”
Section: Introductionmentioning
confidence: 99%
“…Lateral tibial condylar lesions were associated with RR=3.264(95% CI of 1.253 -8.503).. Chondral lesions of patella(14.2%), Trochlea (4.7%)& Lateral femoral condyle( 5.7%) though present, didn't have significant association with delay in surgery. Our observations in 106 patients have limitations in throwing light to association of chondral changes in patella, trochlea and lateral femoral condyle, as compared to some investigators 4,[25][26][27][28] , as the numbers in subtypes were minimal for statistical association. Delay in surgery was also found to have significant association with the presence of intraarticular knee lesions and their number (<3lesions />3 lesions) RR 1.177(CI 1,027-1.349),P-.02 .…”
Section: Discussionmentioning
confidence: 66%
“…Anderson et al recently showed that delays in surgical reconstruction not only resulted in a significant increase in medial meniscal tears and chondral injuries, but more severe injuries as well. These findings were particularly magnified in patients with any pivoting episodes and in patients returning to pivoting sports prior to reconstruction [6]. Guenther et al published similar results in a retrospective series where patients who were reconstructed greater than a year after their injury had a higher incidence of medial meniscus tears and were more likely to have a bucket-handle tear [14].…”
Section: Natural Historymentioning
confidence: 87%
“…The natural history of the untreated ACL deficient knee in the pediatric population is somewhat controversial, but mounting evidence suggests that delays in reconstruction result in greater meniscus tears and cartilage pathology [6,14]. Anderson et al recently showed that delays in surgical reconstruction not only resulted in a significant increase in medial meniscal tears and chondral injuries, but more severe injuries as well.…”
Section: Natural Historymentioning
confidence: 99%